Consumption of ultra-processed foods and cancer risk: results from NutriNet-Santé prospective cohort. (14th February 2018) - Fiolet, Thibault; Srour, Bernard; Sellem, Laury; Kesse-Guyot, Emmanuelle; Allès, Benjamin; Méjean, Caroline; Deschasaux, Mélanie; Fassier, Philippine; Latino-Martel, Paule; Beslay, Marie; Hercberg, Serge; Lavalette, Céline; et al.
Abstract: Objective: To assess the prospective associations between consumption of ultra-processed food and risk of cancer. Design: Population based cohort study. Setting and participants: 104 980 participants aged at least 18 years (median age 42.8 years) from the French NutriNet-Santé cohort (2009-17). Dietary intakes were collected using repeated 24 hour dietary records, designed to register participants' usual consumption for 3300 different food items. These were categorised according to their degree of processing by the NOVA classification. Main outcome measures: Associations between ultra-processed food intake and risk of overall, breast, prostate, and colorectal cancer assessed by multivariable Cox proportional hazard models adjusted for known risk factors. Results: Ultra-processed food intake was associated with higher overall cancer risk (n=2228 cases; hazard ratio for a 10% increment in the proportion of ultra-processed food in the diet 1.12 (95% confidence interval 1.06 to 1.18); P for trend<0.001) and breast cancer risk (n=739 cases; hazard ratio 1.11 (1.02 to 1.22); P for trend=0.02). These results remained statistically significant after adjustment for several markers of the nutritional quality of the diet (lipid, sodium, and carbohydrate intakes and/or a Western pattern derived by principal component analysis). Conclusions: In this large prospective study, a 10% increase in the proportion of ultra-processed foods in the diet was associated with a significant increase of greater than 10% in risks of overall and breast cancer. Further studies are needed to better understand the relative effect of the various dimensions of processing (nutritional composition, food additives, contact materials, and neoformed contaminants) in these associations. Study registration: Clinicaltrials.gov NCT03335644 .